Clothing and fashion in southern history - Ownby, Ted; Walton, Becca (University Press of Mississippi, 2020)
"Contributions by Grace Elizabeth Hale, Katie Knowles, Ted Ownby, Jonathan Prude, William Sturkey, Susannah Walker, Becca Walton, and Sarah Jones Weicksel Fashion studies have long centered on the art and preservation of finely rendered garments of the upper class, and archival resources used in the study of southern history have gaps and silences. Yet, little study has been given to the approach of clothing as something made, worn, and intimately experienced by enslaved people, incarcerated people, and the poor and working class, and by subcultures perceived as transgressive. The essays in the volume, using clothing as a point of departure, encourage readers to imagine the South's centuries-long engagement with a global economy through garments, with cotton harvested by enslaved or poorly paid workers, milled in distant factories, designed with influence from cosmopolitan tastemakers, and sold back in the South, often by immigrant merchants. Contributors explore such topics as how free and enslaved women with few or no legal rights claimed to own clothing in the mid-1800s, how white women in the Confederacy claimed the making of clothing as a form of patriotism, how imprisoned men and women made and imagined their clothing, and clothing cooperatives in civil rights-era Mississippi. An introduction by editors Ted Ownby and Becca Walton asks how best to begin studying clothing and fashion in southern history, and an afterword by Jonathan Prude asks how best to conclude"--